Endovascular treatment of fenestration of the posterior communicating artery with an aneurysm at the same site: case report and review of the literature - Zheng, Yuxing; Hu, Antong; Gao, Ziyun (Frontiers in Radiology, 2025)
BackgroundThe anatomical definition of fenestration in the posterior communicating artery (PCoA) has long been contentious. Previously reported cases exhibiting “dual-origin” characteristics more closely align with partial duplication, resulting in a lack of definitive clinical evidence for true fenestrations. This study presents the first globally reported case of a PCoA fenestration confirmed by multimodal imaging and co-occurring with an aneurysm at the same site, providing critical evidence for establishing imaging diagnostic criteria for fenestrations.Case presentationA 65-year-old woman presented with persistent dizziness. Digital subtraction angiography (DSA) revealed a localized fenestration at the origin of the left PCoA, with a saccular aneurysm arising proximal to the fenestrated segment. Intraoperative 3D rotational angiography definitively characterized the fenestration as an interruption in a single vessel wall without parallel vascular structures (excluding partial duplication). The aneurysm was successfully treated via endovascular coil embolization, achieving Raymond-Roy Class I occlusion. No recurrence was observed at 12-month follow-up (mRS score 0).ConclusionThis study establishes the first imaging diagnostic criteria for PCoA fenestration, demonstrating that it can be distinguished from partial duplication by the key radiological feature of “single-vessel-wall interruption.” Embryologically, PCoA fenestration likely results from abnormal fusion of primitive embryonic vascular plexuses, with hemodynamic disturbance at the fenestration site identified as a critical mechanism for aneurysm formation. This case suggests the potential safety and efficacy of endovascular intervention proved safe and effective for managing intracranial aneurysms associated with arterial fenestration at the same location.